Optimal window design for W-OFDM - Khawar Hussain; R. López-Valcarce (IEEE Int. Conf. Acoustics, Speech and Signal Processing (ICASSP), 2020)
Windowing is an effective approach to reduce out-of-band radiation (OBR) in multicarrier systems in order to avoid adjacent channel interference. However, commonly used window functions are chosen in an ad hoc manner and fixed. We present an optimal window design for windowed-OFDM minimizing OBR within a given frequency region. The proposed technique is flexible in that it allows to specify the range of frequencies involved in the minimization and to apply spectral weighting. The optimal window can be computed offline.
Keywords: spectrum shaping; winter